(untitled) (Perspectivas em Ciência da Informação, 2025)
Open Government Data is part of initiatives that seek to promote transparency, participation, and collaboration between governments and society. Among the challenges that emerged from this movement are the growing volume of information generated or held by governments, and the urgency of information management. In this work, we investigate the Governmental Information Management that subsidizes the publication of Open Government Data and propose a Digital Curation model aimed at the specificities of the public sector. With a qualitative approach, we adopted the case study and the harmonization between different models to propose a new curation model. The results comprise the case study, the harmonized Digital Curation model, and the validation carried out through use scenarios. We conclude that the fast technological evolution, the dynamics of public management, the lack of public policies, and low popular support heighten the difficulties governments face. The harmonized curation model for Government Open Data contributes to addressing some of these challenges, in particular by prioritizing the strengthening of interaction between the community and the government, in addition to offering a set of theories and practices aimed at the selection and arrangement of data, aiming at its preservation, use, and future reuse.